Profiling bacterial communities of irrigation water and leafy green vegetables produced by small-scale farms and sold in informal settlements in South Africa - D. M. Kgoale; J. K. Gokul; S. Duvenage; E. M. Du Plessis; L. Korsten (CABI Agriculture and Bioscience)
Abstract Morogo is an African indigenous term used for leafy green vegetables harvested in the wild or cultivated in small-scale farms and consumed by the local populations of the region. Small-scale farmers have gained recognition as important suppliers of morogo to informal settlements. In commercial production systems, leafy green vegetables have increasingly been reported as associated with foodborne pathogens and disease outbreaks. Little is known of the presence of these organisms on leafy green vegetables in the informal unregulated food systems. This study aimed to profile bacterial communities in irrigation water (flooding and overhead irrigation water) and leafy green vegetables (Brassica rapa L. chinensis and Brassica rapa varieties of morogo) to establish the natural bacterial flora at the water-fresh produce interface from five small-scale farms in two provinces in South Africa. Illumina MiSeq high-throughput sequencing showed that each farm exhibited a unique bacterial community composition, with an overall high relative abundance of Proteobacteria, Firmicutes and Actinobacteria, including prominent families such as Burkholderiaceae (48%), Enterobacteriaceae (34%), Bacillales Family XII (8%), Rhodobacteraceae (3%), Micrococcaceae (1.98%) and Pseudomonadaceae (1.79%). Specific Enterobacteriaceae Serratia, Enterobacter, Salmonella, Shigella, Escherichia coli, Buchnera, Citrobacter, Klebsiella and Proteus were identified, in addition to unique communities associated with plant or irrigation water source. These findings suggest that the edible plant microbiome can play an important role as transient contributor to the human gut and has the potential to affect overall health.